English Language Acquisiton by Treader in Sanggigi Beach: A Study of Ethnography - Sri Martini; Palar, Dwianita Conny; Mutria Farhaeni (HAMJAH DIHA FOUNDATION bekerjasama dengan PENA INSTITUTE, 2024)
In this research discusses how English is learned by beach traders in Sanggigi, Indonesia. The globalization and technology on the rise, having strong English skills is becoming increasingly important to be competitive in various fields, including tourism. This study uses qualitative methods, specifically ethnography study, to examine how these traders acquire English language. The research explores two main approaches: formal education (courses, high school) for those with a traditional learning background, and informal learning through listening, remembering, imitating, and direct interaction for those without formal schooling. Based on the results of data analysis conducted by researcher, can conclude that the second language acquisition on the beach traders Sanggigi is through several processes, namely: traders who have a formal education base in obtaining a second language, such as Following Course Institution, high school and second language that can be through lectures. and traders who do not have a formal school education background get a second language through Listening, Remembering and Imitating, and experience directly.